A study of the effect of soaking faba bean seeds in several treatments on germination, some morphological and physiological growth characteristics, and their tolerance to salt stress. - Suad Mohammed Al-Siriti; Alsbani, Aya Ali; Naima Mohammed (AlQalam Journal of Medical and Applied Sciences, 2025)
This study evaluated the effect of soaking broad bean Vicia faba L. seeds in various treatment solutions (calcium chloride (CaCl₂) at 1% and 0.5% concentrations, gibberellic acid (GA) at 1000 and 500 mg/L, salicylic acid (SA) at 0.5% and 0.25%, and water soaking) for 24 hours, compared to a control group (no soaking). The goal was to mitigate the negative impact of irrigation water salinity on seed germination and certain morphological and physiological growth traits of broad beans. The results showed that seeds soaked in 1% and 0.5% calcium chloride solutions achieved a 100% germination rate. Calcium chloride soaking enhanced the seeds’ tolerance to salt stress by improving vital metabolic activities, which stabilized cell membranes. Post germination, these seeds also exhibited resistance to the adverse effects of salinity (induced by 0.1% sodium chloride irrigation) across all studied traits. For instance, the highest shoot lengths (53 cm with freshwater irrigation and 48.7 cm with 0.1% NaCl irrigation) were recorded in seeds soaked in 1% CaCl₂. Additionally, significant increases were observed in total plant height, internode distance, fresh shoot weight, and stem thickness compared to other treatments, and leaf area compared to the control. These improvements ultimately enhanced chlorophyll (a) and (b) levels, boosting photosynthetic efficiency. Although irrigation with 0.1% NaCl reduced these values compared to freshwater irrigation, indicating that salt stress hindered cell expansion, seed soaking in optimal CaCl₂ concentrations alleviated this effect. This supports calcium’s role in enhancing plant salt tolerance by strengthening cell membranes and wall. In contrast, seeds treated with gibberellic acid and salicylic acid showed very poor germination, likely due to the excessive concentrations used, which negatively impacted seed viability.